RITU (SEASON), RITUCHARYA AND PRAKRITI- A CONCEPTUAL STUDY - Nilesh Ganeshrao, Bakal; Dattatraya Somaji, Lode; Aparna Shrikrishna, Patil (International Journal of Ayurveda and Pharma Research, 2015)
The Prakriti (genetic constitution) and Kala (season) are extra ordinarily related with each other from the origin of a Prakriti due to many common and mutual factors. Naturally the effect of Kala on the Prakriti is unavoidable. The off springs from the conjugation of same Sukra (sperm) and Shonita (ovum) are not alike by Prakriti, because the time of conception or fertilization of the ovum might be different. The prominent Doshas during the time of conception has got definite role in the formation of Prakriti during conception, as well as after birth also. If the time predominates the Vata dosha, there must be certain qualities of Vata Dosha, even though the conjugating Sukra and Shonita may be of different Dosha. In such cases the chances of mixed Prakriti is more. The Charakacharya said that, a chance of Sama prakriti find is very difficult or rare. Most of the Prakrities are Vatala, Pittala and Sleshmala with predominance of Vata, Pitta and Kapha respectively. The season has great role in the genetic constitution because the fertilization of ovum also depends upon the time. Sushruta said, after the cessation of the Rajo darshana (menstrual period) the 12 nights are useful for fertilization only. The modern physiology also states that the mature ovum get discharged through one of the two ovaries, every month, on or around the 14th day of cycle and so the period round about the 14th day is best for definite conception. This clearly shows the relation of Kala (season) and Prakriti (genetic constitution) since its origin and again ahead throughout the life time. Nowadays, the nature is changing its qualities due to various atmospheric changes like pollution, space experiments, heavy industrialization and population crisis. So while studying the effects of Kala (season) one has to face the hyper/ hypo and perverted faculties of Kala (season) which are affecting the generations. So the study of Kala (season) in respect of its various effects on Prakriti (genetic constitution), will be the essential thing in future. As per Ayurveda, Ritucharya (seasonal lifestyle) should be followed for prevention of diseases arising from variations in Tridosha due to Kala (season). In present study, we tried to advocate Ritucharya (seasonal lifestyle) with respect to Prakriti (genetic constitution).